Diversamente scienza Atti del convegno su genere e scienza, organizzato dalla Conferenza nazionale degli organismi di parità e dal CUG dell'Università di Firenze il 12 ottobre 2018 - Tomio, Patrizia; Casalini, Brunella (Comitato Unico di Garanzia, 2020)
This work originates from the conference organized by the Equity and Diversity Committee of the University of Florence and the National Conference of the Gender Parity Organisms of the Italian Universities held in Florence the 12th October 2018. The papers here collected illustrate the obstacles that women encounter in their academic career, especially in the STEM (Science, Technology, Engineering, and Mathematics). The issues the volumes deals with are still worth taking into consideration considering that women represent only the 30% of the academic research staff at the world level and that only the 30% of women students choose STEM faculties.